2016
DOI: 10.1590/1679-78251831
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Analysis of a Magnetoelectroelastic Rectangular Plate Based on a Higher-Order Shear Deformation Theory

Abstract: Free vibration of a magnetoelectroelastic rectangular plate is investigated based on the Reddy's third-order shear deformation theory. The plate rests on an elastic foundation and it is considered to have different boundary conditions. Gauss's laws for electrostatics and magnetostatics are used to model the electric and magnetic behavior. The partial differential equations of motion are reduced to a single partial differential equation and then by using the Galerkin method, the ordinary differential equation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…39 Considering this, Moita et al 40 attempted to evaluate the frequencies of three-layered MEE rectangular plates through higher-order FE formulation. A similar analysis was performed by Lage et al 41 The effect of elastic foundation on the variation of the coupled dynamic response of MEE plates was studied by Shooshtari and Razavi 42 via analytical solutions. Through HSDT and making use of the FE platform, several studies related to the influence of material properties and geometric variations on the coupled frequency response of MEE plates were conducted by Vinyas et al 4345 Also, few attempts have been made to examine the influence of electromagnetic (EM) boundary conditions on the coupled responses of FG porous MEE 46 and CNT-based MEE shells.…”
Section: Introductionmentioning
confidence: 85%
“…39 Considering this, Moita et al 40 attempted to evaluate the frequencies of three-layered MEE rectangular plates through higher-order FE formulation. A similar analysis was performed by Lage et al 41 The effect of elastic foundation on the variation of the coupled dynamic response of MEE plates was studied by Shooshtari and Razavi 42 via analytical solutions. Through HSDT and making use of the FE platform, several studies related to the influence of material properties and geometric variations on the coupled frequency response of MEE plates were conducted by Vinyas et al 4345 Also, few attempts have been made to examine the influence of electromagnetic (EM) boundary conditions on the coupled responses of FG porous MEE 46 and CNT-based MEE shells.…”
Section: Introductionmentioning
confidence: 85%
“…A number of publications are devoted to the development of various model bodies (for instance, beams [7], rods [8,19], plates [9][10][11][12], and shells [13][14][15][16]) that take into account effects of electromagnetoelastic coupling. Zhang et al [7] developed a model of transversely isotropic electromagnetoelastic Timoshenko beams by using a variational formulation based on Hamilton's principle, an extended modified theory of couple stresses, and a two-parameter model of elastic foundation.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the electric and magnetic potentials have opposite effect on the natural frequencies. Shooshtari and Razavi [9] studied application of Reddy's higher-order shear deformation theory to magnetoelectroelastic vibration analysis of a rectangular plate with various boundary conditions based on Galerkin method. Raissi et al [10] applied various higher-order shear deformation theory to stress analysis of a simply supported square sandwich plate subjected to uniform transverse loads.…”
Section: Introductionmentioning
confidence: 99%